Institutionalizing and patronizing science: A history of the founding of Bataviaasch Genootschap - Darojat, Muhamad Hasan (Patra Widya: Seri Penerbitan Penelitian Sejarah dan Budaya., 2024)
This article discusses an effort to advance sciences for the public benefit through institutionalization of knowledge production and a significant role of government patronage for science. With the support of the VOC colonial government, Jacob Cornelis Matthieu Radermacher founded Bataviaasch Genootschap der Konsten en Wetenschappen on April 24, 1778, for the advancement of arts and sciences in the Dutch colonies. Using the historical method, this study aimed to construct a historical understanding in explaining the founding of the first European learned society in the Asian colonies. The study found that European experience of institutionalization of knowledge production and establishment of the scientific information exchange network was a significant factor in the founding of BG and that the role of the VOC government’s support was very significant to the point that BG’s foundation became possible due to that support and the lack of it led to BG’s temporary decline in activity from 1792 to 1812.